Предмет: Алгебра,
автор: Marat00000007
(y-4)(y+2)-(y-2)^2=-30
Ответы
Автор ответа:
0
(y -4)(y+2) -(y -2)² = -30
y² -2y -8 -(y² -4y +4)= -30
y² -2y -8 -y² +4y -4 = -30
2y -12 = -30
2y = -30 +12
2y = -18
y = -18/2
y = -9
y² -2y -8 -(y² -4y +4)= -30
y² -2y -8 -y² +4y -4 = -30
2y -12 = -30
2y = -30 +12
2y = -18
y = -18/2
y = -9
Похожие вопросы
Предмет: Геометрия,
автор: 0507072007
Предмет: Химия,
автор: eosjshb
Предмет: Математика,
автор: andreiostrovec73
Предмет: Математика,
автор: lena11939
Предмет: Информатика,
автор: ГеЛя203